Correction: Mini-review on an engineering approach towards the selection of transition metal complex-based catalysts for photocatalytic H2 production. Issue 13 (19th June 2019) - Huo, Jingpei; Zhang, Yu-Bang; Zou, Wan-Ying; Hu, Xiaohong; Deng, Qianjun; Chen, Dongchu
Abstract : Correction for 'Mini-review on an engineering approach towards the selection of transition metal complex-based catalysts for photocatalytic H2 production' by Jingpei Huo et al., Catal. Sci. Technol., 2019, 9, 2716–2727.